Peran Notaris dalam Menjaga Keamanan Data Pribadi di Era Digital - Dicky Fachrul Ulum; Rusdianto Sesung (Lembaga Pengembangan Kinerja Dosen, 2024)
In maintaining the security of personal data in the digital era, it is very important to remember that personal data can be used by unauthorized parties for various purposes. This is like the notary profession which is now required to be able to maintain the security of each client's data. Notaries can participate in recording important digital documents, such as deeds and contracts, which can help prevent manipulation. Due to the problems that occur, of course the role of the notary in maintaining data security must be considered, especially in transactions and legal documents. Even though the digital world has changed the way many transactions are carried out, the role of notaries still plays an important role in ensuring the validity, integrity and security of digital documents. Notaries can witness and certify contracts and digital legal documents, making them legally valid. The aim of this research is to explain and analyze the role of notaries in maintaining the security of personal data in the digital era. The approach used in this research is a juridical-empirical approach. The results of this research are that the role of notaries in maintaining data security in the digital era has an important role in validating digital signatures. By verifying identity and ensuring that digital signatures are valid, notaries help ensure security in digital transactions. In addition, notaries can also provide digital certificates that confirm the validity of digital signatures and electronic documents. This certificate is a strong proof of authentication. This is proof that the Notary ensures that digital transactions comply with applicable laws, including data privacy regulations and cyber security regulations. This helps keep data secure.